Molecular evolution and functional characterisation of haplotypes of an important rubber biosynthesis gene in Hevea brasiliensis - Thomas K.U; Anantharamanan R; Ravindran M; Saha T (Plant Biology, 2016)
Hydroxy-methylglutaryl coenzyme-A synthase (HMGS) is a rate-limiting enzyme in the cytoplasmic isoprenoid biosynthesis pathway leading to natural rubber production in Hevea brasiliensis (rubber). Analysis of the structural variants of this gene is imperative to understand their functional significance in rubber biosynthesis so that they can be properly utilized for ongoing crop improvement programmes in Hevea. We report here allele richness and diversity of the HMGS gene in selected popular rubber clones. Haplotypes consisting of single nucleotide polymorphisms (SNPs) from the coding and non-coding regions with a high degree of heterozygosity were identified. Segregation and linkage disequilibrium analysis confirmed that recombination is the major contributor to the generation of allelic diversity, rather than point mutations. The evolutionarily conserved nature of some SNPs was identified by comparative DNA sequence analysis of HMGS orthologues from diverse taxa, demonstrating the molecular evolution of rubber biosynthesis genes in general. In silico three-dimensional structural studies highlighting the structural positioning of non-synonymous SNPs from different HMGS haplotypes revealed that the ligand-binding site on the enzyme remains impervious to the reported sequence variations. In contrast, gene expression results indicated the possibility of association between specific haplotypes and HMGS expression in Hevea clones, which may have a downstream impact up to the level of rubber production. Moreover, haplotype diversity of the HMGS gene and its putative association with gene expression can be the basis for further genetic association studies in rubber. Furthermore, the data also show the role of SNPs in the evolution of candidate genes coding for functional traits in plants.
Keywords: Haplotype structure; Hevea brasiliensis; HMGCoA synthase; Isoprenoid biosynthesis; SNPs